In Vitro Studies on the Virulence of Spodoptera Litura Baculovirus - Mohammed Hussein, Syakira (2003)
Baculoviruses have been used as biopesticides against economic pests in agriculture, forestry and landscapes. In vitro production of baculoviruses has often been considered especially because of the ease of large-scale propagation. In this study, in vitro production was investigated by the infectivity of two genera of baculoviruses, Nucleopolyhedrosis virus (NPV) and Granulovirus (GV) to cultured lepidopteran cells. Production of baculoviruses depends on the ability of these cells to replicate in an optimal condition. Spodoptera litura baculovirus isolated locally was investigated for its virulence to two cell lines by inoculating with both forms of the virus, occlusion-body derived virions (PDV) and budded virus (BV), from SpltNPV and SpltGV. Efforts to develop cell cultures from the local Spodoptera litura for use in replicating these local baculoviruses was, however, unsuccessful due to cell deterioration or microbial contamination. A cell line from Spodoptera Jrugiperda (S£9) was susceptible to budded virus obtained directly from the insect, but not to viral progeny. While these results suggest Sf9 cells have potential for replicating these baculoviruses, the Spodoptera litura cell line, TUAT -Spli-221 appeared not to be susceptible.